Systemic Lupus Erythematosus: An Overview of Pathogenesis, Prevalence, Diagnosis, Classification Criteria, Management, Challenges, and Future Directions - Balid Albarbar; Hanan Aga; Sabri M. Shalbi (Khalij-Libya Journal of Dental and Medical Research, 2024)
Systemic Lupus Erythematosus (SLE) is a complex, chronic autoimmune disease characterized by widespread inflammation and tissue damage across multiple organ systems. This paper aims to review the SLE pathogenesis, prevalence, diagnosis, classification criteria, management, challenges, and future directions. Scientific literature pertaining to SLE was analyzed through comprehensive searches in specialized academic resources, including PubMed and Google Scholar. This review explores the multifaceted nature of SLE, pathogenesis, which involves a complex interplay of genetic, environmental, and immunological factors leading to the loss of self-tolerance and autoantibody production. The epidemiology section highlights the varying incidence and prevalence of SLE globally. We review current diagnostic approaches, including clinical evaluation and laboratory tests, which are crucial for early and accurate diagnosis. The classification criteria, as outlined by established guidelines, are discussed to provide insight into the diagnostic framework used to identify and categorize SLE. SLE management is briefly addressed, including issues related to disease heterogeneity. Finally, we explore future directions in SLE research, focusing on emerging therapies. Despite advancements, the management of SLE remains challenging, necessitating ongoing research efforts to improve diagnostic precision, therapeutic efficacy, and patient outcomes. الذئبة الحمامية الجهازية هي مرض مناعي ذاتي مزمن معقد يتميز بالتهاب واسع النطاق وتلف الأنسجة عبر أنظمة أعضاء متعددة. تهدف هذه الورقة إلى مراجعة مسببات مرض الذئبة الحمامية الجهازية وانتشاره وتشخيصه ومعايير التصنيف والعلاج والتحديات والأفاق المستقبلية. تم مراجعة البحوث العلمية المتعلقة بمرض الذئبة الحمامية الجهازية من خلال عمليات بحث شاملة من المصادر الأكاديمية المتخصصة، بما في ذلك PubMed وGoogle Scholar. يستكشف هذا الاستعراض الطبيعة المتعددة الأوجه لمرض الذئبة الحمامية الجهازية، والمسببات المرضية، والتي تنطوي على تفاعل معقد بين العوامل الوراثية والبيئية والمناعية التي تؤدي إلى فقدان تحمل الذات وإنتاج الأجسام المضادة الذاتية. يسلط جزء علم الأوبئة الضوء على التفاوت في حدوث وانتشار مرض الذئبة الحمامية الجهازية على مستوى العالم. نستعرض طرق التشخيص الحالية، بما في ذلك التشخيص السريري والاختبارات المعملية، والتي تعد حاسمة للتشخيص المبكر والدقيق. تم مناقشة معايير التصنيف، كما هو موضح في المبادئ التوجيهية المعمول بها، لتوفير نظرة حول التشخيصي المستخدم لتحديد وتصنيف مرض الذئبة الحمامية الجهازية. تم تناول إدارة مرض الذئبة الحمامية الجهازية بإيجاز، بما في ذلك تنوع أو اختلاف في كيفية ظهور المرض أو تطوره بين الأفراد. أخيرًا، نستكشف الأفاق المستقبلية في أبحاث الذئبة الحمامية الجهازية، مع التركيز على العلاجات الناشئة. وعلى الرغم من التقدم، لا تزال إدارة مرض الذئبة الحمامية الجهازية تشكل تحديًا، مما يستلزم بذل جهود بحثية مستمرة لتحسين دقة التشخيص وفعالية العلاج للمرضى